O processo do luto no psicodrama bipessoal - Formiga, Marcelle Napoleão do Rêgo (2009)
This present research is a theoretical study about the Attachment Theory, mourning process and Psychodrama Theory Its purpose is to submit for theoretical considerations about the Attachment Theory and Psychodrama and describe the bipersonal psycho dramatic psychotherapy with patients in mourning. From the description of the Attachment Theory and Psychodrama, we submit considerations about the interface between theses two areas of knowledge and describe bipersonal Psychodrama as a significant psychotherapy method with patients in mourning. This essay contributions are that the Attachment Theory and Psychodrama are complementary and, together, assist the development of psychotherapy consistent. We believe that the Attachment Theory is a solid theory that helps the work of the psycho dramatist with mourners